Exploring the role of biomass-derived carbon quantum dots: Hydrothermal carbonization, bioimaging in vivo/in vitro, and biomedical application - Yuni Aldriani Lubis (Bioculture Journal, 2026)
Background: Carbon-based nanoparticle classes consisting of various subgroups based on morphology and crystallinity are called carbon dots (CQDs). The physical, chemical, and optical properties of CQDs can be modified using the simple pot synthesis technique. Additionally, its non-toxic nature, biocompatibility, physical and chemical responsiveness, resistance to chemical and photo bleaching, and low cost make it suitable for various purposes, such as biomedical imaging applications. Biomass waste, which has been widely discarded without economic utilization and potential, can surprisingly be used as a precursor for CQDs. Method: The literature was systematically collected from major databases. Studies from 2017–2025 were analyzed based on synthesis strategies, surface functionalization, and biological performance. Its potential in the medical field is highly advantageous. CQDs have fluorescence that is useful for biomedical imaging both in vivo and in vitro. The hydrothermal carbonization approach is also discussed in more detail, highlighting its green and sustainable synthesis, as well as the ease of the synthesis process. Finding: It was found that CQDs have compatibility and adjustable optical properties. Its fluorescence can clearly record tissues, body care, aging, and living cells. Utilizing renewable biomass precursors offers an environmentally friendly and cost-effective route for synthesizing fluorescent nanoprobes with excellent water solubility, tunable emission, and low cytotoxicity. Additionally, in vitro studies reinforce CQDs as multicolor fluorescent probes, and in vivo studies demonstrate that CQDs have low toxicity, rapid clearance, are safe, and biocompatible. Conclusion: This paper delves into the remarkable potential of CQDs to provide insights into how fluorescent inks are truly essential in biomedical imaging. Novelty/Originality of this article: This study provides a comprehensive and updated synthesis of CQD research spanning up to 2025, specifically focusing on the transition from "waste to nanoprobe."